Livelihood Risk Adaptation Among Local Maize Farmers in Guluk-Guluk Madura Indonesia (A PLS-SEM Approach) - Anisah Anisah; Cepryana Sathalica Widyananda; Tirta Yoga (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Local maize serves as a vital source of both food security and household income across various regions of Indonesia, particularly in Sumenep, Madura. However, efforts to sustain agricultural livelihoods are increasingly challenged by a range of risks. One of the most pressing issues is the growing prevalence of hybrid maize cultivation in Madura, which has adversely affected local farmers who continue to grow traditional maize varieties to meet their subsistence needs. Given these challenges, farmers need to develop and implement strategic responses by leveraging their available livelihood assets in order to mitigate risks and adopt adaptation strategies suited to their specific context. This study aims to develop a risk management and adaptation framework for maize farmers in the Guluk-Guluk area of Madura, taking into account their livelihood assets. The research was conducted in Guluk-Guluk, a location purposively selected based on regional differences in maize productivity. The study took place from October 2023 to March 2024 and involved 51 local maize farmers selected via random sampling with a 1% margin of error. The study assessed several forms of farmers' resources, including labor capacity, material assets, community networks, environmental conditions, and economic means, along with their adjustment practices, such as diversifying activities and modifying planting timelines. Risk variables included technological and natural risks. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The findings indicate that the resources supporting farmers' livelihoods play a meaningful and beneficial role in shaping how corn growers in the area manage risks and adjust their practices. The findings also indicate that the most commonly adopted adaptation strategy is diversification. Technological risk emerged as the most significant risk faced by farmers, while financial capital was found to be the most influential asset in supporting risk response and adaptation efforts.